2007
DOI: 10.1038/sj.npp.1301327
|View full text |Cite
|
Sign up to set email alerts
|

Acetaldehyde, a Major Constituent of Tobacco Smoke, Enhances Behavioral, Endocrine, and Neuronal Responses to Nicotine in Adolescent and Adult Rats

Abstract: We have previously shown that acetaldehyde, a constituent of tobacco smoke, increases nicotine self-administration in adolescent, but not adult, rats. The aim of this study was to determine whether acetaldehyde influences other behavioral, endocrine, or neuronal responses to nicotine at either age. Juvenile (postnatal day (P) 27) and adult (P90) male Sprague-Dawley rats were treated with saline, acetaldehyde (16 mg/kg/injection  2, i.v.), nicotine (30 mg/kg/injection  2, i.v.) or a combination of acetaldehyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
47
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 47 publications
(61 reference statements)
8
47
3
Order By: Relevance
“…Our data confirm and extend a previous finding that adolescents have greater nicotineinduced activation in the NAc shell (Shram et al, 2007). Although acute nicotine does not induce c-fos in BLA of adult animals (Cao et al, 2007a;Valjent et al, 2002;MathieuKia et al, 1998), we now show an adolescent-specific nicotine-induced activation of the BLA.…”
Section: Adolescent Maturation Of the Mesocorticolimbic Systemsupporting
confidence: 92%
See 1 more Smart Citation
“…Our data confirm and extend a previous finding that adolescents have greater nicotineinduced activation in the NAc shell (Shram et al, 2007). Although acute nicotine does not induce c-fos in BLA of adult animals (Cao et al, 2007a;Valjent et al, 2002;MathieuKia et al, 1998), we now show an adolescent-specific nicotine-induced activation of the BLA.…”
Section: Adolescent Maturation Of the Mesocorticolimbic Systemsupporting
confidence: 92%
“…Two intravenous injections of nicotine (2 Â 30 mg/kg/0.1 ml), or saline, spaced 1 min apart, were administered daily for 4 consecutive days during early adolescence (P28-31), late adolescence (P37-40), or adulthood (P86-89). The daily nicotine dose used yields peak serum levels of approximately 30 ng/ml in both adolescents and adults (Cao et al, 2007a), which is well within the range of the average smoker. Intravenous injections of S-15535 (2 Â 15 or 2 Â 150 mg/kg) and 8-OH-DPAT (2 Â 5 mg/kg) were administered during early adolescence (P28-31).…”
Section: -Day Pretreatmentmentioning
confidence: 63%
“…Moreover, parallel to other addictive drugs (cocaine and heroin), nicotine releases a neurotransmitter called dopamine, in the brain. Dopamine triggers an optimistic feeling in smokers and affects the brain pathway that controls reward and pleasure [19]. As a small amount of data revealed that cigarette smoke can reduce anxiety in some smokers, the correlation between smoking and anxiety is complicated.…”
Section: Effect Of Cigarette Smoke On Depression and Anxietymentioning
confidence: 99%
“…NM_053354.3 CAGATGTTCCATGCACACT TGTGGATGTAGGAAAGTTGCA GAPDH AB017801.1 TCCCTCAAGATTGTCAGCAA AGATCCACAACGGATACATT environment and has been widely used to evaluate anxiogenic and anxiolytic effects of a drug in rodents (Cao et al, 2007;Frye et al, 2008;Prut and Belzung, 2003). As described by Cao et al (2007), each animal was placed into a 75 cm  75 cm white Plexiglas arena and videotaped continuously for 30 min to quantify time-dependent behaviors.…”
Section: Genementioning
confidence: 99%